PENERAPAN PERAN NENEK TERHADAP PEMBERIAN MAKANAN PENDAMPING ASI: Application Of Grand's Role In Supporting Breast Milk - Tutik Hidayati (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2022)
Proper feeding practices are of fundamental importance to the survival, growth, development, health and nutrition of infants and children. Complementary food for breast milk (MP ASI) is additional food given to infants after the age of 6 months to the age of 24 months to meet nutritional needs other than breast milk. Breast milk should still be given to babies, at least until the age of 24 months. The role of supplementary food is not as a substitute for breast milk but to complement or accompany breast milk. Support factors for other family members, including grandmothers who give advice according to the culture and habits of the local community, such as giving water, banana honey to babies or other foods that are not suitable for the child's age, are still difficult to eliminate, and can also influence the practice of early complementary feeding so that it affects the growth and development of children. . The purpose of this study was to analyze the application of the role of grandmothers in complementary feeding. The design used in this study was cross sectional. Population All mothers who have babies 0-12 months in Gading Village are 46 people. The sample in this study are all mothers who have babies 0-12 months in Gading Village totaling 46 people. The sampling technique used is total sampling. The measuring instrument used in this study was a questionnaire to measure the role of grandmothers. Univariate data analysis using frequency distribution. Bivariate data analysis using chi square. The results of the study obtained a value of value = 0.000 which means it is smaller than 0.05 so that the influence of the application of the role of grandmothers on the provision of complementary feeding